When ethics runs counter to morals - Pina-Cabral, Joao (2021)
In the present conjuncture, Brazilian social anthropologists are facing a major challenge to their work. I suggest that this happens because of anthropology’s central dependence on the ethnographic method. The ethnographer’s direct contact with the people they study gives rise to an ethical response that moves the ethnographer beyond abstract moral principles. But, in the world of Jair Bolsonaro or Donald Trump, ethics counters morals: the objectivized, legalistic formulas favored by these autocratic ideologues (supposedly representing “tradition” and “identity”) turn out not to correspond to the actual conditions that face the persons that anthropologists meet in the field, who experience oppression and suffering in their lives.